(untitled) (KULT_online, 2019)
Aidan Smith’s Gender, Heteronormativity, and the American Presidency places gender at the center of the U.S.-American political landscape. Revisiting the medial self-presentation of presidential candidates from 1952 to 2016, Smith takes these campaign communications as frames for negotiating notions of gender normativity and its appeal for the U.S.-American electorate. This interdisciplinary book combines approaches and concepts from media studies, gender studies and political science, and argues that contenders for the highest office in the United States rely on traditional gender norms for legitimizing their claims for power.